The Study of Living Hadith on Reciting Surah Al-Waqi'ah Tradition at Pesantren Tebuireng: Studi Living Hadis atas Tradisi Pembacaan Surah al-Waqi'ah di Pesantren Tebuireng - Ananda Prayogi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Islamic religious traditions in Indonesia carried out by a group of muslim communities ideally have legitimacy from valid legal sources. Interestingly, most of them do not fully understand this source but they believe in its benefits, as is the tradition of reciting Surah al-Waqi'ah which is carried out routinely at Pesantren Tebuireng which is believed to bring property based on a hadith. Using a descriptive quantitative approach, this research examines the level of understanding and trust of the students towards the activities carried out and the hadith behind based on the theory of living hadith studies. In addition, the test employs Bloom's taxonomy theory as an approach to evaluate activities based on a questionnaire. The goal, this research can provide a clear statistical description of the related problems. As a result, the students on average already have strong beliefs in terms of their affective and psychomotor aspects. However, in the cognitive aspect, it still needs to be improved so that later the tradition and the legal sources behind them can be properly integrated